THEORETICAL BASIS OF ORGANIZATION OF MANAGEMENT SYSTEM OF SOCIO-ECONOMIC DEVELOPMENT OF MUNICIPAL STRUCTURE (World Bulletin of Management and Law, 2022)
In the article, the need to develop scientific and methodological support for improving the management mechanisms of socio-economic development of municipal (local) structures, the need to develop approaches to effective state and local management, and the need to achieve the national goals of transformation were studied. The purpose of the research is to develop and substantiate theoretical, methodological and practical recommendations for improving the mechanisms of managing the socioeconomic development of local structures. Generalization and comparison, statistical, economic and mathematical modelling methods for evaluating the results were used in the work to determine the most effective approaches to assessing the management of the socio-economic development of local structures.
Keywords: institutional structure; improvement of management mechanisms; local structures